2020
DOI: 10.1186/s12936-020-03468-2
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the unreached: effectiveness and satisfaction with community-directed distribution of sulfadoxine-pyrimethamine for preventing malaria in pregnancy in rural South-East, Nigeria

Abstract: Background Innovative community strategies to increase intermittent preventive treatment with sulfadoxine-pyrimethamine (IPTp-SP) coverage is advocated particularly in rural areas, where health infrastructure is weakest and malaria transmission highest. This study involved proof-of-concept implementation research to determine satisfaction with and effectiveness of community-directed distribution of IPTp-SP on uptake among pregnant women in Ebonyi State, Nigeria. Methods This before-and-after study was carrie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Reduced queues in the health facilities was cited as the main reason for this disposition [ 18 ]. The high levels of acceptability closely match with the postintervention satisfaction levels with the community-directed distribution of IPTp intervention [ 19 ].…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Reduced queues in the health facilities was cited as the main reason for this disposition [ 18 ]. The high levels of acceptability closely match with the postintervention satisfaction levels with the community-directed distribution of IPTp intervention [ 19 ].…”
Section: Discussionmentioning
confidence: 75%
“…Community involvement and ownership is critical to the success of community-level projects [ 12 ]. The successful implementation of the community-directed distribution of sulfadoxine-pyrimethamine project in the study community was mostly hinged on the positive attitude and cooperation shown by the community members who were actively involved in the project [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations